(untitled) (Indian Journal of Animal Production and Management, 2024)
The present study was conducted to assess the effect of two sides of North-South oriented shed with open area in East and West directions on microclimatic variables, physiological & behavioural responses and semen quality in Frieswal bulls. Adult breeding bulls (24) were distributed equally into East (GE) and West (GW) facing opening sides of the shed. All the bulls were kept in individual pens under loose housing system and were managed with uniform management practices. The average THI values during hot-dry and hot-humid seasons were in the various levels of thermal stress in both the groups. During hot-dry and hot-humid seasons, physiological responses in GW bulls were higher in the afternoon than in the morning values, however, in GE bulls rectal temperature and respiration rate increased significantly in the afternoon Sperm concentration was higher (p<0.05) during hotter part of the year than during comfort or cooler. The bulls of both the groups spent maximum time on rumination on kachcha floor while sitting (40 and 37.5% in GE and GW, respectively). In the GE, bulls spent more time on other minor activities during summer than in winter. In GW, bulls spent more time in covered area during summer during day time. Semen volume and initial sperm motility was found better during hot-dry and winter months. Post thaw sperm motility improved during comfort and winter months. The results revealed that semen quality and dry matter intake of experimental bulls did not show any significant effect due to design of sheds.